Pengaruh Electronic Word of Mouth (e-WOM) terhadap Keputusan Pembelian Konsumen pada Smartphone Infinix Indonesia - Salma, Siti Nur’aida (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
This research aims to measure how much influence Electronic Word of Mouth (e-WOM) has on purchasing decisions on Infinix Indonesia smartphones. This research method uses a quantitative method using primary data sources (Questionnaires) and secondary data (Scientific Papers). The sample in this study consisted of 100 respondents, namely Infinix smartphone users who were followers of the @infinixid Instagram account using the Probability sampling method with Simple random sampling. The data analysis process uses simple regression analysis with the SPSS 25 data processing tool. The research results show that the Electronic Word of Mouth variable consisting of Intensity, Valence of opinion, and content has a positive and significant effect on the Purchasing Decision Variable.